"L'Utopie serait-elle institutionnalisée?": Georges Perec at the Moulin d'Andé. Issue 2 (15th March 2019) - Gabel, Aubrey
Abstract: This essay offers a much-needed history of the Moulin d'Andé, a utopian community in Normandy that welcomed an array of political, intellectual, and artistic figures. In particular, it focuses on a few collaborative projects that came out of the Moulin d'Andé, which were helmed by Georges Perec: Christine Lipinska's photographs for Perec's long-form poem La Clôture (1976), Bernard Queysanne and Perec's filmic adaptation of Perec's novel Un homme qui dort (1973), and Perec's novel La Disparition (1969). By analyzing how these various projects understood and enacted the process of collaboration, this essay considers what kinds of community practice were fostered by the Moulin d'Andé.